Parasitic Diseases Schistosomiasis - El Ridi, Rashika (IntechOpen, 2013)
Reports on schistosomiasis epidemiology and clinical features in Africa and Brazil, and development of novel drugs that affect the worm tegument, and vaccine based on excretory-secretory products and Type 2 cytokines.